INKATHA WARRIOR MASCULINITIES - Suttner, Raymond (PINS-Psychology in Society, 2025)
Waetjen, T (2004) Workers & warriors. Masculinity and the struggle for nation in South Africa. Cape Town: HSRC Press. ISBN 13 978-0769-2171-0. Pages 168. This book is a reprint of an American edition of the same work published in 2004 (Waetjen, 2004). The HSRC Press is to be commended for bringing out the book in paperback format and at an affordable price. The work presents some very important ideas, hitherto neglected, to my knowledge, about the notion of home in homeland and the way in which gender relations have played themselves out in Inkatha politics. It also explores a range of ways in which Buthelezi and Inkatha sought to contest the hegemony of the United Democratic Front/African National Congress/Congress of South African Trade Unions by appealing to specific notions of masculinity based on relatively static notions of what “being Zulu” requires. In many cases, these notions interfaced well with opposition to militant and particularly guerrilla struggles and also coexisted well with the concerns preoccupying capital from the late 1970s to separate the objections to apartheid from the continued existence of capitalism.